The Visual Worlds of Social Network Sites Images and image-based communication on Facebook and Co. (Volume 4) - Autenrieth, Ulla P.; Neumann-Braun, Klaus (Nomos Verlagsgesellschaft mbH & Co. KG, 2011)
The central form of communication on social network sites (sns) is the communication with and through images. Accordingly, the present volume highlights images and image-based communication on sns, such as Facebook, and on nightlife platforms, such as Tilllate. First, the authors analyze the two central image categories in depth - profile images and photo albums. What follows is the portrayal of dramaturgical and staging strategies of the (semi) professional photography on the nightlife platforms, which leads to an evaluation of the importance of the international glamour photography as a parameter of private photographic self-expression. Other questions that the authors ponder in the volume are: Which functions and meanings do images have for the communications between users on social network sites? To what extent could certain design characteristics in the image-based communication on sns establish themselves as prototypical staging patterns? Which staging traditions are followed thereby? Which staging strategies are followed on different online platforms by the users' (self) visualizations?